2017
DOI: 10.1002/lary.26963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medialization laryngoplasty on dynamic nanomechanical vocal fold structure properties

Abstract: NA. Laryngoscope, 128:1163-1169, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Due to material nonlinearity, stretching of the vocal folds around the implant would significantly increase vocal fold stiffness in the transverse plane. This may explain the stiffness increase reported in a recent indentation study [19]. Previous studies have shown that increasing transverse stiffness may increase phonation threshold pressure and reduce the vertical phase difference and thus the closed quotient of vocal fold vibration [20], which may be undesirable, but may also suppress vocal instabilities [21].…”
Section: Discussionmentioning
confidence: 82%
“…Due to material nonlinearity, stretching of the vocal folds around the implant would significantly increase vocal fold stiffness in the transverse plane. This may explain the stiffness increase reported in a recent indentation study [19]. Previous studies have shown that increasing transverse stiffness may increase phonation threshold pressure and reduce the vertical phase difference and thus the closed quotient of vocal fold vibration [20], which may be undesirable, but may also suppress vocal instabilities [21].…”
Section: Discussionmentioning
confidence: 82%
“…[1][2][3] Indentation biomechanical testing techniques show promise in both animal models and engineered vocal fold products to objectively assess material stiffness and elasticity. [4][5][6][7][8] Comparison between excised human and canine vocal fold cover layers identified similar stiffness and elastic properties measured via Young's modulus. 5 These preliminary studies provided useful biomechanical information, but are time-consuming and traditionally require significant tissue dissection or disruption.…”
Section: Introductionmentioning
confidence: 77%
“…Unique laryngeal geometry and pliability of vocal fold tissues create a challenging environment for biomechanical testing approaches . Indentation biomechanical testing techniques show promise in both animal models and engineered vocal fold products to objectively assess material stiffness and elasticity . Comparison between excised human and canine vocal fold cover layers identified similar stiffness and elastic properties measured via Young's modulus .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations